Dental Anatomy and Occlusion: Maxillary Incisors - Jan Mitchell; Rhoda Sword; Martha Brackett; Mario Romero (Association of American Medical Colleges, 2016)
Abstract Introduction This introductory dental anatomy module begins the process of teaching dental students how to analyze the structure and form of human teeth, a skill that is foundational to all subsequent areas of restorative dentistry. This module is an interactive preclinical activity that allows the learner to master the important morphologic and functional features of human maxillary incisors, as well as to become familiar with common clinical anomalies. Methods As the first in a series of dental morphology lectures, it includes basic skills that are applicable to later modules. The lab waxing activity, which follows the 40-minute lecture, requires two 4-hour sessions. Since this is one of the first hand-eye coordination technique labs in dental school, it is an early opportunity to teach dental laboratory procedures and safety, as well as the level of attention to detail required in dentistry. The goal of the exercise is to create a wax model of tooth #8 on a commercially available simulated preparation. To aid the student, there is a video of the steps of a correct wax-up and a grading rubric with specific expectations. Results Comparing the 3 years before the introduction of the module improvements with the 3 years after, the average percentage of A grades more than doubled (from 17.1% to 38.5%), while the average percentage of failures also doubled (from 7.0% to 14.5%), identifying the struggling students who needed additional help. The opinion from student tutors, who themselves were graded under the previous grade form, is that the new rubric clarified expectations, thus improving practice and performance. Discussion While the exercise had been a part of the instructional course for many years, the introduction of the video and, particularly, the rubric has improved the students' understanding of the specific expectations of the task, simplified the grading, reduced the time spent explaining grades, and reduced student concerns that the grades were subjective.